GAMBARAN PEMAHAMAN TENTANG STERILISASI ALAT KESEHATAN GIGI PADA MAHASISWA TINGKAT II JURUSAN KEPERAWATAN GIGI (Jurnal Kesehatan Siliwangi, 2021)
In the practice of health services, sterilization is an absolute thing to do. Sterilization is a way to free something (tools, materials, media, etc.) from microorganisms that are not expected to be present (bacteria, fungi, viruses and spores).  Sterilization of dental and oral health equipment is very important for health workers, especially clinical students to increase awareness of the susceptibility to cross infection.  Students who have entered the clinical period as one of the dental and oral health workers, must have an understanding of the sterilization of dental and oral health equipment before starting dental and oral health measures. This type of research is descriptive research using primary data obtained through filling out questionnaires using google forms which aims to Description of Understanding About Sterilization of Dental Equipment in Students of Dental Nursing. The results showed that students' understanding of dental and oral health sterilization of 86 respondents 29.1% had an understanding with good criteria, 68.6% had an understanding with sufficient criteria, and 2.3% had an understanding with low criteria. Many factors influence respondents' understanding, although in this study students have received material and lessons at the same time by the same teacher, but because each individual has different thinking skills in understanding the material, it causes results in research.  this is different too.